An Equilibrium Model of Credit Rating Agencies - Steinar Holden; Gisle James Natvik; Adrien Vigier (Norges Bank, 2012)
We develop a model of credit rating agencies (CRAs) based on reputation concerns. Ratings affect investors' choice and, thereby, also issuers' access to funding and default risk. We show that - in equilibrium - the informational content of credit ratings is inferior to that of CRAs' private information. We find that CRAs have a pro-cyclical impact on default risk: in a liquidity boom CRAs help resolve investors' coordination problem, and lower the probability of default; in a liquidity crunch CRAs raise the probability of default. Furthermore, rating standards tend to be pro-cyclical, while biased CRA-incentives will ultimately be self-defeating.
hdl:11250/2496816
Keywords: G24; G33; D82; C72; 330; CRA; credit rating agencies; global games; coordination failure